2020
DOI: 10.1002/apj.2435
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrogen‐enriched biogas induction on combustion, performance, and emission characteristics of dual‐fuel compression ignition engine

Abstract: Gaseous fuel induction in a compression ignition (CI) engine has picked up much attention over the most recent few years, particularly when it is produced by using renewable sources. In this study, hydrogen-enriched biogas (HEB) was used as a gaseous fuel and co-combusted in dual-fuel CI engine.Experimentation was carried out on a 3.5-kW CI engine test rig in the brake mean effective pressure range between 0 and 3.5 bar, as well as, HEB between 0.1 and 0.5 kg/hr. HEB induction effects on various engine charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…As evidence that the industrial process is based on renewable energy, hydrogen (H 2 ) is considered to have the lowest carbon footprint and the highest efficiency production energy. The combustion of H 2 produced water vapour, and did not emit PM, CO or HC, because the carbon content was zero within the structure of the H 2 composition [44]. The auto ignition for H 2 did not occur easily in modern internal combustion engines throughout compression stroke, because H 2 required higher temperature to initiate the preignition and lower cetane number in comparison of diesel fuel.…”
Section: Hydrogen As Fuel Supplementmentioning
confidence: 99%
See 2 more Smart Citations
“…As evidence that the industrial process is based on renewable energy, hydrogen (H 2 ) is considered to have the lowest carbon footprint and the highest efficiency production energy. The combustion of H 2 produced water vapour, and did not emit PM, CO or HC, because the carbon content was zero within the structure of the H 2 composition [44]. The auto ignition for H 2 did not occur easily in modern internal combustion engines throughout compression stroke, because H 2 required higher temperature to initiate the preignition and lower cetane number in comparison of diesel fuel.…”
Section: Hydrogen As Fuel Supplementmentioning
confidence: 99%
“…Addition of various proportions of H 2 to the blends of biogas increased the PCP due to highly combustion ability. Rosha et al [44] showed that addition of H to natural gas (NG) blends at higher loading operations increased the PCP.…”
Section: Analysis Of Combustion Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Against the background of the global energy crisis and environmental pollution, all countries are vigorously developing new energy vehicles and formulating more stringent emission regulations. Except for speeding up the electrification process of vehicles, seeking renewable and cleaner alternative fuels for traditional internal combustion engines or adding various additives to traditional fuels to improve their combustion and emission characteristics is also an important way to solve current energy and environmental problems. , …”
Section: Introductionmentioning
confidence: 99%